Correction: Development of Glioblastoma from Stem Cells to a Full-Fledged Tumor - Pavel Vladimirovich NIKITIN; Guzel Railevna MUSINA; Valery Nikolaevich POLOZOV; Dmitry Nikolaevich GOREIKO; Vladimir Mikhailovich KRASNOVSKY; Leonard WERKENBARK; Mauric KJELIN; Piotr Sergeevich TIMASHEV (Federation of Turkish Pathology Societies, 2023)
After the publication of the original article, authors noticed that the authors' the surnames and patronymics (middle names) had been written in incorrect order. The correct order and spelling of the authors' names is as belows and the original article has been corrected accordingly.